2010
DOI: 10.1002/ijc.25255
|View full text |Cite
|
Sign up to set email alerts
|

The antitumor activity of the fungicide ciclopirox

Abstract: Ciclopirox olamine (CPX) is a synthetic antifungal agent clinically used to treat mycoses of the skin and nails. Here, we show that CPX inhibited tumor growth in human breast cancer MDA-MB-231 xenografts. To unveil the underlying mechanism, we further studied the antitumor activity of CPX in cell culture. The results indicate that CPX inhibited cell proliferation and induced apoptosis in human rhabdomyosarcoma (Rh30), breast carcinoma (MDA-MB231) and colon adenocarcinoma (HT-29) cells in a concentration-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(136 citation statements)
references
References 34 publications
6
130
0
Order By: Relevance
“…Of note, IG 50 values of about 1-10 mM detected in CPX-treated NB cells are pharmacologically achievable (Weir et al, 2011;Minden et al, 2014). The CPX-mediated effect on viability of NB cells resulted from a combination of cell cycle deregulation and induction of apoptosis, corroborating previously published data on other tumor cell types (Zhou et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Of note, IG 50 values of about 1-10 mM detected in CPX-treated NB cells are pharmacologically achievable (Weir et al, 2011;Minden et al, 2014). The CPX-mediated effect on viability of NB cells resulted from a combination of cell cycle deregulation and induction of apoptosis, corroborating previously published data on other tumor cell types (Zhou et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, CPX exerted inhibition of DOHH in HUVEC and HeLa cells in a concentration-dependent manner with IC 50 values of 5 and 6.25 mM, respectively (Clement et al, 2002;Mémin et al, 2014), coincident with the dose threshold region of CPX effects observed in CHP134 cells. In addition to DOHH, the G 1 arrest induced by CPX could be mediated by multiple mechanisms involving cyclin D1, CDK2, RB1, and CDK inhibitor p21 CIP1/WAF1 (Zhou et al, 2010). However, the link between these proteins and upstream irondependent events remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…N1-guanyl-1,7-diaminoheptane (GC7) and ciclopirox olamine (CPX) are potent inhibitors of deoxyhypusine synthase, which catalyzes eIF5A hypusination. GC7 and CPX have shown antiproliferative effects in various cell lines (137,138) and antitumor activity in vivo in breast cancer, melanoma, leukemia, and myeloma models (139)(140)(141).…”
Section: Targeting Deregulated Translation In Cancermentioning
confidence: 99%
“…It inhibits tumor growth in human breast cancer MDA-MB-231 xenografts, it inhibits cell proliferation and induces apoptosis in human rhabdomyosarcoma (Rh30), breast carcinoma (MDA-MB231) and colon adenocarcinoma (HT-29) cells and inhibits Wnt/betacatenin signaling in myeloma. Ciclopirox-induced apoptosis of cancer cells is mediated, at least in part, through a caspasedependent mechanism [100]. Griseofulvin has similar chemical features as compared with ciclopirox olamine.…”
Section: Therapeutic Potentialsmentioning
confidence: 99%